PENGGUNAAN METODE PROSES HIRARKI ANALITIK (PHA) DALAM PEMILIHAN LOKASI UNTUK RELOKASI BANDARA RAHADI OESMAN KETAPANG KALIMANTAN BARAT - Rudi S. Suyono, . (Fakultas Teknik Universitas Tanjungpura, 2010)
Kabupaten Ketapang has an airport that named the Rahadi Oesman Airport. This airport owning location situation which less profit for the development of service activities of air transportation in the future because its location residing in midst of Kabupaten Ketapang and also located reside in the nearby resident settlement. This condition generates the serious problem like noise resulted from aircraft sound whether in its takeoff or landing position that can endanger the resident near the airport location. Therefore it is required to be conducted a study to chosen the other; dissimilar location for the relocation of the airport. This study identify the criterion used in choosing the optimal airport location pursuant to technical aspect, aspect of operational and safety operate for the air transport environmental aspect and. In this study is selected three alternative locations that planned the new airport location, the locations are Desa Tempurukan, Desa Suka Bangun, and Desa Pesaguan. The survey conducted with the respondent amount as much 200 people. Analyze for the decision making of to use the method Process The Analytic Hierarchy (PHA), that is an model capable to coordinate entire problem of decision making to chosen one most optimal location. This assessment done by comparing a number of combinations from element exists in each hierarchy level. Assessment conducted by comparing component of pursuant to assessment scale. From result analyst obtained by pursuant to obtained technical criterion of most optimal alternative location is Desa Tempurukan with the percentage is equal to 35%, Desa Suka Bangun equal to 34% and Desa Pesagunan equal to 30%. Pursuant to criterion of operational and safety operate for the air transport obtained a most optimal alternative location is Desa Tempurukan with the percentage equal to 42%, Desa Suka Bangun equal to 38% and Desa Pesaguan equal to 20%. While pursuant to obtained environmental criterion of most optimal alternative location is Desa Tempurukan with the percentage equal to 58%, Desa Pesaguan equal to 25% and Desa Suka Bangun equal to 17%. So that the conclusion from the result got one most optimal new Ketapang Airport location is Desa Tempurukan.